Assessment of Allergen-Induced Respiratory Hyperresponsiveness before the Prescription of a Specific Immunotherapy. Issue 2 (June 2015) - Olivier, Celso Eduardo; Argentão, Daiana Guedes Pinto; Lima, Regiane Patussi dos Santos; da Silva, Mariana Dias; Gonçalves dos Santos, Raquel Acácia Pereira; Fabbri, Natalia
Background: Asymptomatic sensitization is a frequent condition that must be considered before the indication of allergic-specific immunotherapy. Objective: The aim of this study was to appreciate and correlate the local and spirometric changes elicited by the allergen-specific nasal provocation test (NPT) to define practical and feasible guidelines for the allergist/immunologist to demonstrate specific respiratory hyperresponsiveness before the indication of allergic-specific immunotherapy. Methods: A total of 172 subjects (children and adults) with a diagnosis of allergic rhinitis were submitted to flow-volume spirometry immediately before and after the NPT performed with Dermatophagoides antigens. The differences between the pre- and postspirometric estimated values of peak expiratory flow rate (PEFdif% ), forced expiratory volume in 1 second (FEV1dif% ), and forced vital capacity (FVCdif% ) were correlated with the results of the nasal provocation test symptom score (NPT-SS). Results: There were 119 subjects (69%) with NPT-SS > 2. Among these patients who were reactive, the mean NPT-SS was 6.3. The Spearman's correlation between PEFdif% and NPT-SS was r = −0.44 (p = 0.01); the Spearman's correlation between FEV1dif% and NPT-SS was r = −0.22 (p = 0.01), and the Spearman's correlation between FVCdif% and NPT-SS was r = −0.21 (p = 0.04). Conclusion: The combined utilization of the allergen-specific NPT-SS with the spirometry (or PEF meter) is a safe methodology to evaluate allergen-specific nasal and bronchial hyperresponsiveness (which sometimes acts as a bronchial provocation test) in patients with allergic rhinitis and asthma due to hypersensitivity who are candidates for allergen-specific immunotherapy.